Factors related to Health-Related Quality of Life (HRQoL) of elderly people in Tehran - Darvishpoor Kakhki, Ali; Abed saeedi, Jilla (Advances in Nursing & Midwifery, 2014)
Abstract Background and Aim: Aging is associated with variety of challenges and tensions which could possibly affect Quality of life of older people. This study was conducted to describe factors and HRQoL of elderly people in Tehran city. Method and Materials: This descriptive correlational study was conducted on elderly people of Jahandidegan Centers of Tehran. The sample of the study consisted of 400 elder persons which were selected by stratified sampling method. Demographic questionnaire and Iranian versions of short from health survey (SF-36) scale were used for data collection. Content validity was used to assess the validity of the instrument and Cronbach’s alpha was computed for internal consistency.Data were analyzed with SPSS software. Findings: 75% of elderly people were female and 25% male with a mean age of 67.65(± 6.38) year. The mean scores for quality of life domains ranged from11.22 (±9.5) for role physical function to 63.83(± 25.02) for social function. The scores of quality of life domains were significantly correlated with age, gender, marital status, education level, number of family members living with the elder person and number of physician visits. Conclusion: The findings of this study showed that HRQoL of elder people is lower than expect and related to some factors. So, developing plans to improvement of health status and HRQoL of elderly people is necessary. Key words: Elderly People, Health-Related Quality of life, Health, Aging, Tehran.